Community health intervention project active ageing-ripen into health - Banza, Maria Manuela Serra (2013)
Objective: to implement the intervention project: Active Ageing – Ripen into Health, based upon a partnership of the Unidade de Cuidados na Comunidade (UCC) / Universidade Sénior. Method: methodology of the project, based on the ®Work Breakdown Structure. Documentary research was used. The data collection was carried out with the target population and stakeholders. The target population was constituted by the 23 students signed in the project. Two questionnaires were applied to them (The Method of Biopsychosocial Evaluation, from the Portuguese National Network for Integrated Continuous Care - Rede Nacional de Cuidados Continuados Integrados (RNCCI) and another one with the purpose to identify the suitable education needs for health); a questionnaire was made to the stakeholders (Identification of the suitable education needs for health) as well an interview was performed. The collected data have been subjected to statistical treatment and content analysis. Results: the analysis of the results obtained, allowed to structure an Intervention Programme based upon the National (Portugal) guidelines for the health of elderly people, suitable for the targeted, the available resources as well our purposes and final objective. Conclusion: The objectives were reached: the partnership proposed was implemented and the Intervention Programme is being carried out. The project promoted the reflexion and the work of the multidisciplinary and inter-sectoral team in the community; at the same time, it pointed out to the attention for the individual and collective responsibilities in response to problems related to active ageing. Viewing that the nurses of community health are key elements on the group intervention in all the stages of the life cycle, either due to their multi-sectoral framework or by all the knowledge they acquired, this way, the key factors were converged to become it a successful project, so, actually contributing for gains in health, based on the healthy aging.